MENINGKATKAN MINAT BELAJAR MELALUI PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA SPINWHEEL - Putri, Viona Audia (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2025)
This study aims to increase students' learning interest by using the Spinwheel-based Problem-Based Learning (PBL) model in history lessons, as well as to assess the effectiveness of the implemented Spinwheel-based PBL model in history learning. Data collection techniques used in this study include observation, interviews, questionnaires, and documentation. This type of research is Classroom Action Research (CAR), which involves the stages of planning, action, observation and evaluation, and reflection. The research was conducted in three stages, namely Cycle I, Cycle II, and Cycle III. Data analysis techniques involved normality tests, homogeneity tests, and success criteria tests. Based on the analysis of the research results and discussion, it can be concluded that the implementation of the Spinwheel-based Problem-Based Learning model in history learning is effective in increasing the learning interest of Grade XI students in Phase F.2.